Kajian Inklusivitas dalam Prespektif Green Social Work - Ramdani, Jaka (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
This study aims to analyze the relevance and potential application of the Green Social Work (GSW) approach in supporting inclusive and sustainable development in Jakarta Province. The research employed a systematic literature review method using a qualitative approach. Literature was selected through the keywords